(untitled) (Acta Structilia, 1998)
The Department of Public Works leases close on two million square metres of office space for state departments in South Africa. The department follows an extensive lease evaluation process. including a multifaceted evaluation on aspects such as suitable depth of space versus natural light, appropriate electrical distribution for the planned office layout and an evaluation of the amount of partitioning that will be required as a function of shape on plan. A questionnaire survey was conducted among Public Works Department leasing officials to establish the extent and depth of their knowledge of these factors. It was concluded that the existing lease evaluation has many strong points. The survey results, however, indicated serious limitations to the existing understanding of leasing officials of crucial aspects in the evaluation process. Proposals are presented to improve on the process in general.